reformar la ley de la jurisdicción contencioso administrativa incorporando el recurso de apelación de las sentencias de primera instancia - Valdez Quezada, Jorge Luis (2016)
The Administrative Jurisdiction under Ecuadorian law, as part of Administrative Law, is a little-or poorly treated and studied it mildly; both writers as legal professionals, even more so on the weaknesses or loopholes that being old issue has not been addressed and updated to the new legal needs of society. The Administrative Court is the judicial body to monitor that properly meets the performance of the administration; likewise controls the resolutions of conflicts between management and managed, is why, to make use of the rights we have as citizens, there are different remedies to challenge issues of illegality, or when they affect rights or when they have seen injured by the poor performance of public administration. In our legislation, the Administrative Court, is single instance, has jurisdiction to hear disputes that are made against the acts, deeds and regulations emanating from the administration, the failure originates to be single instance, is breached the rights of the citizens as the principle of double instance like the appeal. The fundamental basis of study and analysis is the Law of Administrative Jurisdiction, legal instrument that regulates the administrative contentious procedure, and that in our academic study will resolve it in different conceptual, legal, doctrinaire frameworks and alternative solutions that are intended to address this legal problem also analyzed from the field of comparative law.